Landasan Akuntabilitas Ilmiah dalam Etika Penggunaan dan Pengembangan Kecerdasan Buatan (AI): Analisis QS. Al-Isrā’ [17]:36 - Putri, Lintang Dewi Fi’liya (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3779, 2025)
The development of artificial intelligence represents one of the key milestones in the modern technological revolution, bringing profound impacts on systems of knowledge, ethics, and humanity. Amidst these advancements, serious challenges arise concerning scientific accountability, algorithmic transparency, and moral responsibility in technology-based decision-making processes. This study aims to examine the relevance of QS. Al-Isrā’ [17]:36 as a Qur’anic value foundation for establishing principles of scientific accountability in the development and application of artificial intelligence. The method employed is thematic exegesis (tafsīr mawḍū‘ī) using a Qur’anic ethical approach, exploring the meanings of as-sam‘, al-baṣar, and al-fu’ād as symbols of the integration between rational, empirical, and moral aspects within Islamic epistemology. The findings indicate that QS. Al-Isrā’ [17]:36 emphasizes the importance of trust, transparency, and accountability in every scientific and technological activity. These values reflect the Qur’anic guidance that humans should not merely be users of technology but also guardians of ethics and scientific integrity. Thus, the verse provides a normative framework for developing artificial intelligence that upholds the principles of public benefit, justice, and spiritual responsibility.